Advanced Nebulizer Designs Employing Vibrating Mesh/Aperture Plate Technologies for Aerosol Generation - Waldrep, J. C.; Dhand, R. (Current Drug Delivery, 2008)
Recent technological advances and improved nebulizer designs have overcome many limitations of jet nebulizers. Newer devices employ a vibrating mesh or aperture plate (VM/AP) for the generation of therapeutic aerosols with consistent, increased efficiency, predominant aerosol fine particle fractions, low residuals, and the ability to nebulize even microliter volumes. These enhancements are achieved through several different design features and include improvements that promote patient compliance, such as compact design, portability, shorter treatment durations, and quiet operation. Current VM/AP devices in clinical use are the Omron MicroAir, the Nektar Aeroneb, and the Pari eFlow. However, some devices are only approved for use with specific medications. Development of “smart nebulizers” such as the Respironics I-neb couple VM technologies with coordinated delivery and optimized inhalation patterns to enhance inhaled drug delivery of specialized, expensive formulations. Ongoing development of advanced aerosol technologies should improve clinical outcomes and continue to expand therapeutic options as newer inhaled drugs become available.
Keywords: nebulizer